Relationship Between Perceived Stress Level, Psychological Flexibility, Depression, and Anxiety in Patients with Acute Myocardial Infarction - Esra Polat; Şükrü Çiriş; Zekiye Çelikbas; Afnan Chaudhry (Medicina)
Background and Objectives: Stress and type A personality are known to be risk factors for the development of acute myocardial infarction (AMI), and depression is both a risk factor for AMI and a prognostic factor. In this study, we aimed to evaluate the relationship between psychological flexibility, perceived stress level, depression, and anxiety in AMI patients. Material and Methods: The study included 89 patients with a diagnosis of AMI and 89 volunteer participants with no previous history of coronary angiography and no diagnosis of AMI. Patients were evaluated with the Acceptance and Action Questionnaire (AAQ)-II, the Hospital Anxiety and Depression Scale (HADS), and the Perceived Stress Scale (PSS)-14. Results: A strong positive statistically significant correlation was found between the Perceived Stress Scale score and HAD-II (r = 0.697 p < 0.001), HAD-Anxiety (r = 0.715 p < 0.001), and HAD-Depression (r = 0.657 p < 0.001) scores. A statistically significant moderate positive correlation was found between the HAD-Depression Scale and HAD-Anxiety (r = 0.593 p < 0.001) and AAQ-II (r = 0.530 p < 0.001) scores. A strong positive statistically significant correlation was found between the HAD-Anxiety Scale and AAQ-II (r = 0.809 p < 0.001) scores. Conclusions: Investigation of psychological flexibility, anxiety, and depression in AMI patients with scales such as AAQ-II, PSS-14, and HADS may help early diagnosis and treatment of individuals at risk for psychiatric disorders.